2019
DOI: 10.4062/biomolther.2019.151
|View full text |Cite
|
Sign up to set email alerts
|

Etoposide Induces Mitochondrial Dysfunction and Cellular Senescence in Primary Cultured Rat Astrocytes

Abstract: Brain aging is an inevitable process characterized by structural and functional changes and is a major risk factor for neurodegenerative diseases. Most brain aging studies are focused on neurons and less on astrocytes which are the most abundant cells in the brain known to be in charge of various functions including the maintenance of brain physical formation, ion homeostasis, and secretion of various extracellular matrix proteins. Altered mitochondrial dynamics, defective mitophagy or mitochondrial damages ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…Our results showed that late passage cultivated astrocytes exhibited functional changes manifested by decreased wound healing capacity. These results are consistent with our previous reports showing the decreased wound healing capacity in aging-induced astrocytes through tenovin-1 or etoposide treatment ( Bang et al ., 2019a , 2019b ). Old satellite cells and tenocytes show impaired migration in vitro similar to aged bone marrow-derived dendritic cells ( Grolleau-Julius et al ., 2008 ; Chang et al ., 2012 ; Collins-Hooper et al ., 2012 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our results showed that late passage cultivated astrocytes exhibited functional changes manifested by decreased wound healing capacity. These results are consistent with our previous reports showing the decreased wound healing capacity in aging-induced astrocytes through tenovin-1 or etoposide treatment ( Bang et al ., 2019a , 2019b ). Old satellite cells and tenocytes show impaired migration in vitro similar to aged bone marrow-derived dendritic cells ( Grolleau-Julius et al ., 2008 ; Chang et al ., 2012 ; Collins-Hooper et al ., 2012 ).…”
Section: Discussionsupporting
confidence: 94%
“…Astrocytes that underwent serial passage cultivation for several times showed aged astrocyte phenotypes. Various studies have reported nuclear enlargement of aged primary astrocytes ( Yoon et al ., 2016 ; Bang et al ., 2019a ). The increased nuclear or cell size in aged cells could be due to the increased macromolecule contents such as DNA, RNA, and proteins ( De Cecco et al ., 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the 90th day in vitro the cells were SA-β-gal-positive and had increased expression of GFAP (Pertusa et al, 2007 ). Recently, it has been documented that treatment of astrocytes with sirtuins's inhibitor, tenovin-1 (Bang et al, 2019b ), or etoposide (Bang et al, 2019a ), increased SA-β-gal-positive cell number, induced the senescence-associated secretory phenotype, including increased expression of IL-6 and IL-1β, and of cell cycle-related proteins, such as phospho-histone H3 and CDK2 (Bang et al, 2019a ). Others showed that in human astrocytes induced to senesce by X-irradiation, there was downregulation of genes encoding glutamate and potassium transporters.…”
Section: Senescence Of Glial Cellsmentioning
confidence: 99%
“…Studies have shown that cultured human astrocytes displayed both increased levels of γH2AX and formation of SAHFs (Myung et al, 2008;Bitto et al, 2010;Souza et al, 2015;Seoane et al, 2017; Figure 1). Senescent astrocytes showed nuclear enlargement, which is generally present in specific cell types such as fibroblasts and CNS cells (Yoon et al, 2016;Bang et al, 2019). When DNA damage and DNA repair occur during the cell cycle, the size of the cell and nucleus is slightly increased (Amodeo and Skotheim, 2016).…”
Section: Nuclear Changesmentioning
confidence: 99%